DAMPAK ERUPSI GUNUNG SINABUNG TERHADAP PRODUKSI DAN HARGA CABAI MERAH (Capsicum annum L.) (Desa Beganding, Kecamatan Simpang Empat, Kab. Karo) - Nelly Sinaga; Effendi Lubis; Yan Khoriana Sinaga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This research aims at (1) finding the effects before and after the eruption of Sinabung mountain on production of red chili (Capsicum annumL.) in research area, (2) finding the effects before and after the eruption of Sinabung mountain on price of red chili (Capsicum annumL.), (3) finding the income of red chilli ((Capsicum annumL.) after the eruption of Sinabung mountain in research area. This research was conducted in Beganding village, Simpang Empat Sub-district, Karo regency, province of Sumatera Utara. Research sample was done by using Simple Random Sampling as many as 35 respondents from the total population 167 families. Method of data analysis was by paire sample t-test to find the difference between production and price of red chili(Capsicum annum L.)both before and after the eruption of Sinabung mountain and analysis of red chili farmers’ income. Research findings show that there is a significant effect of red chili production in research area both before and after the eruption of Sinabung mountain. The production of red chili before the eruption of Sinabung mountain is as many as 1.932 kg/farmer > 1.342 kg/farmer (after the eruption of Sinabung mountain) in which the difference is 2.237 kg/farmer. The income of chili farming before and after the eruption of Sinabung mountain was categorized “low” and the comparison indicator is UMK Karo Regency in 2017. It is Rp 2.051.267/month, meanwhile UMK Karo regency is Rp 2.619.234,41.